Fostering Listening Skills and Initial Intercultural Communicative Competence in EFL Pre-Service Teachers Through the Use of ICT. (2015)
The increasingly interconnected and knowledge-driven 21st century world calls for groundbreaking changes in language teaching and learning. To convey this objective, the authors of this book cogently fuse key elements within a sound pedagogical proposal that has been carefully designed to demystify the study of intercultural competence in its traditional settings. Not only does their study ne-tune strategies for the development of critical cultural awareness, but it also unveils paths to authentic interaction, critical thinking, and cooperative, collaborative, and self-regulated learning experiences that evolve in an adaptive learner-centered setting. The scenario chosen to expand students’ communicative boundaries is a hypermedia learning environment that invites learners to travel throughout the United States with a dual focus in mind: the development of listening skills and intercultural competence, as well as nurturing a pluralistic view of the learning of English mediated through the use of technologies. Additionally, the study strives to provide groundwork to less restrictive approaches for the inclusion of eective computer-assisted language learning in the classroom, demonstrating that an interdisciplinary integration of agents and knowledge for ecient design and practice is possible. A unique aspect of this book is that it illustrates a myriad of features underpinning the design of the hypertext, which was entirely created and validated by the authors. All in all, this qualitative case study encompasses a wide range of strategic learning stances in the EFLclassroom, and acts in response to the needs of learners (and instructors) seeking a critical and analytical process of understanding and examining culture. I suggest that this book be used as a reference for language and interdisciplinary courses, as well as professional development programs that combine studies of language skills development and culture.